Geometric dimensioning and tolerancing for mechanical design - Cogorno, Gene R. (New York : McGraw-Hill, 2011)
'An up-to-date guide to geometric dimensioning and tolerancing. Written in accordance with the latest revision of the geometric dimensioning and tolerancing (GD&T) standard, ASME Y14.5-2009, this book teaches the principles and practical applications of GD&T in an easy-to-understand manner. Geometric Dimensioning and Tolerancing for Mechanical Design, Second Edition, begins the discussion of each control with a definition, and then describes how the control is specified, interpreted, and inspected. Detailed drawings illustrate the topics discussed. Study questions and problems at the end of each chapter emphasize key concepts and serve as a self-test. Ensure the proper assembly of parts, improve quality, and reduce costs with help from this authoritative resource. Coverage includes: Dimensioning and tolerancing fundamentals Symbols, terms, and rules Datums Form--flatness, straightness, circularity, and cylindricity Orientation--perpendicularity, parallelism, and angularity Position--general, location, and coaxiality Concentricity and symmetry Runout Profile Graphic analysis Strategy for tolerancing parts'--
'Written in accordance with the latest revision of the geometric dimensioning and tolerancing (GD&T) standard, ASME Y14.5-2009, Geometric Dimensioning and Tolerancing for Mechanical Design, Second Edition, teaches the principles and practical applications of GD&T in an easy-to-understand manner. The book begins the discussion of each control with a definition, and then describes how the control is specified, interpreted, and inspected. Detailed drawings illustrate the topics discussed. Study questions and problems at the end of each chapter emphasize key concepts and serve as a self-test. This authoritative resources helps readers ensure the proper assembly of parts, improve quality, and reduce costs'--
Keywords: Engineering drawings -- Dimensioning; Tolerance (Engineering); Machine design